Low-level laser therapy improves visual acuity in adolescent and adult patients with amblyopia - Ivandic, Boris; Ivandić, Tomislav (Photomedicine and laser surgery, 2012)
Objective: The purpose of this study was to examine the effects of low-level laser therapy (LLLT) on visual acuity in adolescent and adult patients with amblyopia. Background data: Currently, amblyopia can be treated successfully only in children. Methods: In this single-blinded, placebo-controlled study, 178 patients (mean age 46.8 years) with amblyopia caused by ametropia (110 eyes) or strabismus (121 eyes) were included. For LLLT, the area of the macula was irradiated through the conjunctiva from 1 cm distance for 30 sec with laser light (780 nm, 292 Hz, 1:1 duty cycle; average power 7.5 mW; spot area 3 mm2). The treatment was repeated on average 3.5 times, resulting in a mean total dose of 0.77 J/cm2. No occlusion was applied, and no additional medication was administered. Best corrected distant visual acuity was determined using Snellen projection optotypes. In 12 patients (12 eyes), the multifocal visual evoked potential (M-VEP) was recorded. A control group of 20 patients (20 eyes) received mock treatment. Results: Visual acuity improved in ∼90% of the eyes treated with LLLT (p<0.001), increasing by three or more lines in 56.2% and 53.6% of the eyes with amblyopia caused by ametropia and strabismus, respectively. The treatment effect was maintained for at least 6 months. The mean M-VEP amplitude increased by 1207 nV (p<0.001) and mean latency was reduced by 7 msec (p=0.14). No changes were noted in the control group. Conclusions: LLLT led to a significant improvement in visual acuity in adolescent and adult patients with amblyopia caused by ametropia or strabismus.